Reduction of Anxiety Levels in Schizophrenia Patients Using Progressive Muscle Relaxation - kuswa, Yanah kuscianah (South East Asia Nursing Research, 2021)
Anxiety neurosis is the most common mental disorder in society. Progressive muscle relaxation is an independent nursing intervention that can be chosen to reduce anxiety in schizophrenia patients. This case study aims to prove that progressive muscle relaxation can help reduce anxiety levels in schizophrenic patients. The study design is descriptive in the form of a case study with a nursing process approach, applying progressive muscle relaxation techniques to schizophrenic patients who experience problems with anxiety levels. The sample was two adult schizophrenic patients who experienced anxiety in Eredah Complex Mental Health Hospital. The patient's anxiety was measured by the Zung-Self Anxiety Rating Scale. The progressive muscle relaxation procedure is performed 2 times over two days with a duration of 20-30 minutes each session. Hemodynamic measurements and anxiety levels were performed pre-post progressive muscle relaxation. The results of the case study showed that progressive muscle relaxation interventions affected reducing patient anxiety levels. The mean score of the patient's anxiety decreased by 30.34% after being given progressive muscle relaxation. Progressive muscle relaxation is effectively applied to schizophrenic patients with anxiety disorders in nursing service settings.